Expression and function of Anoctamin 1/TMEM16A calcium-activated chloride channels in airways of in vivo mouse models for cystic fibrosis research - Hahn, Anne; Salomon, Johanna J.; Leitz, Dominik; Feigenbutz, Dennis; Korsch, Lisa; Lisewski, Ina; Schrimpf, Katrin; Millar-Büchner, Pamela; Mall, Marcus A.; Frings, Stephan; Möhrlen, Frank (Pflügers Archiv, 2018)
Physiological processes of vital importance are often safeguarded by compensatory systems that substitute for primary processes in case these are damaged by gene mutation. Ca2+-dependent Cl− secretion in airway epithelial cells may provide such a compensatory mechanism for impaired Cl− secretion via cystic fibrosis transmembrane conductance regulator (CFTR) channels in cystic fibrosis (CF). Anoctamin 1 (ANO1) Ca2+-gated Cl− channels are known to contribute to calcium-dependent Cl− secretion in tracheal and bronchial epithelia. In the present study, two mouse models of CF were examined to assess a potential protective function of Ca2+-dependent Cl− secretion, a CFTR deletion model (cftr−/−), and a CF pathology model that overexpresses the epithelial Na+ channel β-subunit (βENaC), which is encoded by the Scnn1b gene, specifically in airway epithelia (Scnn1b-Tg). The expression levels of ANO1 were examined by mRNA and protein content, and the channel protein distribution between ciliated and non-ciliated epithelial cells was analyzed. Moreover, Ussing chamber experiments were conducted to compare Ca2+-dependent Cl− secretion between wild-type animals and the two mouse models. Our results demonstrate that CFTR and ANO1 channels were co-expressed with ENaC in non-ciliated cells of mouse tracheal and bronchial epithelia. Ciliated cells did not express these proteins. Despite co-localization of CFTR and ANO1 in the same cell type, cells in cftr−/− mice displayed no altered expression of ANO1. Similarly, ANO1 expression was unaffected by βENaC overexpression in the Scnn1b-Tg line. These results suggest that the CF-related environment in the two mouse models did not induce ANO1 overexpression as a compensatory system.